Portaria PRR5 nº 73, de 25 de abril de 2016 - (:unkn) unknown (DMPF-e, Brasília, DF, 27 abr. 2016, Caderno Administrativo, p. 19., 2016)
Dispensa e designação de servidores para substitutos de função comissionada.